Religious and sexual nationalisms in Central and Eastern Europe : gods, gays, and governments - Sremac, Srđan, 1976-; Ganzevoort, Reinder Ruard, 1965- (Religion and the Social Order, 2015)
Religious and Sexual Nationalisms in Central and Eastern Europe: Gods, Gays, and Governments. presents case studies from some ten countries that serve to explore the ways in which religion, nationalism, and (homo)sexuality intersect in public discourse. It shows how religious leaders, political and social movements, LGBT-organizations, governments, and media negotiate the powers of religion and state in taking position regarding sexual diversity. These negotiations are as much about sexual morality as they are about national identity, anti-EU sentiments, and the efforts of religious institutions to regain power in post-communist societies.